Rapid Therapeutic Drug Monitoring of Voriconazole Based on High-Performance Liquid Chromatography: A Single-Center Pilot Study in Outpatients - Satoru Morikawa; Yusuke Yagi; Moemi Okazaki; Narika Yanagisawa; Tomoaki Ishida; Kohei Jobu; Takumi Maruyama; Takahiro Kato; Miyuki Matsushita; Yu Arakawa; Yuka Yamagishi; Yukihiro Hamada (Antibiotics)
Background/Objectives: Voriconazole (VRCZ) use requires accurate monitoring to avoid suboptimal drug levels and adverse effects. In addition, the appearance of resistant fungal strains is a problem that needs attention. Blood concentration measurement is the monitoring technique of choice; however, it is slow, limiting its clinical application. This study aimed to evaluate the clinical utility of rapid therapeutic drug monitoring (TDM) for VRCZ using high-performance liquid chromatography with ultraviolet detection (HPLC-UV) compared to conventional outsourced liquid chromatography–tandem mass spectrometry (LC-MS/MS) testing in outpatient care. Methods: VRCZ blood concentrations were measured using HPLC-UV and LC-MS/MS. Reporting times, accuracy, and clinical outcomes were assessed for outpatients receiving VRCZ treatment. Safety was monitored for renal, hepatic, and visual toxicities. Results: HPLC-UV significantly reduced reporting times (0.433 h vs. 74.3 h, p < 0.001), and Deming’s regression analyses showed a strong correlation with LC-MS/MS results (Pearson’s r = 0.988). Bland–Altman analysis showed an average difference of 0.025 μg/mL between HPLC-UV and LC-MS/MS. Prospective monitoring of three outpatients revealed no adverse events, enabling safe and effective VRCZ dosing. Conclusions: Rapid VRCZ TDM using HPLC-UV is a cost-effective and feasible approach for outpatient care, significantly improving reporting times and patient safety. Further studies and cross-facility collaboration are needed to expand its application.